2022
DOI: 10.3389/fendo.2022.996863
|View full text |Cite
|
Sign up to set email alerts
|

The causal relationship between obesity and skin and soft tissue infections: A two-sample Mendelian randomization study

Abstract: ObjectiveMany observational studies have shown that obesity strongly affects skin and soft tissue infections (SSTIs). However, whether a causal genetic relationship exists between obesity and SSTIs is unclear.MethodsA two-sample Mendelian randomization (MR) study was used to explore whether obesity is causally associated with SSTIs using a publicly released genome-wide association study (GWAS). An inverse-variance weighted (IVW) analysis was used as the primary analysis, and the results are reported as the odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…It is worth noting the association between obesity and surgical site infection, and surgical site infection will lead to the occurrence of VH. 31 Our study showed that VAT rather than SAT was associated with a high risk of VH, and VAT might serve as a potential predictor of IH. A recently published meta-analysis showed that the prophylactic use of mesh to prevent IH in midline laparotomy could reduce the prevalence of IH and did not increase the prevalence of surgical site occurrence.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…It is worth noting the association between obesity and surgical site infection, and surgical site infection will lead to the occurrence of VH. 31 Our study showed that VAT rather than SAT was associated with a high risk of VH, and VAT might serve as a potential predictor of IH. A recently published meta-analysis showed that the prophylactic use of mesh to prevent IH in midline laparotomy could reduce the prevalence of IH and did not increase the prevalence of surgical site occurrence.…”
Section: Discussionmentioning
confidence: 52%
“…The debate persists regarding whether abdominal subcutaneous or visceral obesity plays a predominant role in IH development. It is worth noting the association between obesity and surgical site infection, and surgical site infection will lead to the occurrence of VH 31 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an English primary care cohort of 85 312 participants with type 1 or type 2 diabetes mellitus found glycaemic control was independently associated with risk of hospitalization for infection 42 . Another study used two‐sample Mendelian randomization in the genome‐wide association study of 171 322 participants and found a causal relationship between obesity and SSTI 43 . Previous studies have also found associations between insulin requirement and risk of infection 44 .…”
Section: Discussionmentioning
confidence: 97%
“…42 Another study used two-sample Mendelian randomization in the genome-wide association study of 171 322 participants and found a causal relationship between obesity and SSTI. 43 Previous studies have also found associations between insulin requirement and risk of infection. 44 Insulin is not a first-line therapy for type 2 diabetes mellitus and is generally initiated after failure of first-line therapies or if firstline therapies are contraindicated (such as in advanced chronic kidney disease).…”
Section: Discussionmentioning
confidence: 97%
“…The I 2 statistic, Cochran's Q statistic for the MR-IVW method, and Rucker's Q statistic for the MR-Egger method were used to determine the heterogeneity of the MR analysis, with I 2 < 50 % or P > 0.05 indicating no heterogeneity [ 28 ]. Finally, leave-one-out analysis was used to examine the influence of individual SNPs on the IVW estimates [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%